The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1007/bf00037367
|View full text |Cite
|
Sign up to set email alerts
|

Surber and kick sampling: a comparison for the assessment of macroinvertebrate community structure in streams of south-western Australia

Abstract: Macroinvertebratecommunity structure was compared in benthic samples taken by Surber and kick methods from a lotic system in south-western Australia. Eleven sites were sampled concurrently in winter, spring and summer 1987.Surber samples contained fewer individuals and more taxa, particularly those with a low frequency of occurrence. This was attributed to the lower surface area, but greater intensity of Surber sampling. It is proposed that the Surber method is more suited to taking cryptic and closely adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 18 publications
0
44
0
5
Order By: Relevance
“…While others have compared small numbers of qualitative to quantitative samples collected at a site (e.g. Storey et al 1991;Kerans et al 1992;Metzeling et al 2003), the relationship between qualitative RBA samples and a thoroughly sampled, and quantitative estimate of community structure has not been explored. Furthermore, there has been no exploration of the factors, such as the traits of taxa that may explain the omission or collection of a taxon, and consequently the variability among replicate RBA samples.…”
Section: Introductionmentioning
confidence: 98%
“…While others have compared small numbers of qualitative to quantitative samples collected at a site (e.g. Storey et al 1991;Kerans et al 1992;Metzeling et al 2003), the relationship between qualitative RBA samples and a thoroughly sampled, and quantitative estimate of community structure has not been explored. Furthermore, there has been no exploration of the factors, such as the traits of taxa that may explain the omission or collection of a taxon, and consequently the variability among replicate RBA samples.…”
Section: Introductionmentioning
confidence: 98%
“…Thought not significant, the kick-net sampler recorded the greatest number of taxa but did significantly poorer than the Surber when densities were compared. Storey et al (1991) found that Surber samples contained fewer individuals and more taxa than kick-net samples, though the sampling device in this case consisted of a D-frame pond net and cannot be directly compared to the two-pole kick-net. The kick-net used in the present study covered the largest area but required considerable skill in raising the net to prevent organisms from passing under the net or rolling off the end.…”
Section: Discussionmentioning
confidence: 95%
“…Decisions about the best sampling device to use in RBPs have been highly discussed in the literature, and Kick nets have been preferred in front of Surber samplers (Storey et al 1991). Kick methods have been recommended in biomonitoring surveys providing semiquantitative or qualitative data, and many environmental agencies decided to use it in their national RBP programmes.…”
Section: Discussionmentioning
confidence: 99%